Propolis extracts in Juiz de Fora, Minas Gerais: Unveiling quality and identity (Research, Society and Development, 2025)
This research aims to analyze the quality of propolis extracts sold in Juiz de Fora, Minas Gerais, verifying the compliance of these products with the standards established in Normative Instruction N° 3, of January 19, 2001, of the Ministry of Agriculture, Livestock and Food Supply (MAPA). Physicochemical parameters were analyzed, including alcohol content, dry extract, phenolic compounds, flavonoids, wax content and antioxidant activity. The results revealed that two samples presented dry extract below the regulatory limit, while three demonstrated low antioxidant activity, indicating a lower concentration of bioactive compounds. Despite the adequacy of the alcohol and wax contents, the variation in the chemical composition reinforces the influence of factors such as botanical origin and processing on the final quality of the product. These findings highlight the need for more rigorous quality control, ensuring the standardization and safety of the extracts marketed.